2005
DOI: 10.1002/ca.20173
|View full text |Cite
|
Sign up to set email alerts
|

The extensor indicis et medii communis

Abstract: The aim of this study was to examine the existence of the extensor indicis et medii communis in detail. Thirty-one randomly selected adult cadavers (62 upper extremities) were examined for this project (22 males and 9 females between the ages 38 and 87). The muscle was observed in 3 of 62 hands, an incidence of 4.8%. One was in the right and the other two were in the left hands. Mean length and width of the muscle belly were 4.5 +/- 0.8 and 0.8 +/- 0.3 mm, respectively. Although the muscle did not have a junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…Yalçin et al [47] stated that the common origin of the EIP and the EMP and the occurrence of the EIMC suggest a single embryologic origin of these muscles. Straus [39] demonstrated that the EMP or EIMC is frequently found in the Old World monkey, whereas they are variable in humans.…”
Section: Comparative Anatomy and Phylogenymentioning
confidence: 98%
See 2 more Smart Citations
“…Yalçin et al [47] stated that the common origin of the EIP and the EMP and the occurrence of the EIMC suggest a single embryologic origin of these muscles. Straus [39] demonstrated that the EMP or EIMC is frequently found in the Old World monkey, whereas they are variable in humans.…”
Section: Comparative Anatomy and Phylogenymentioning
confidence: 98%
“…The overall prevalence of EIP Twenty-one studies reported the prevalence of EIP [1,2,4,6,7,10,12,15,16,18,19,21,24,26,29,32,42,47,48,50] with a total of 3858 hands and a PPE of 96.5 % (95 % CI 0.928-0.989, I 2 = 96.2 %). The prevalence of the EIP in the included studies is shown in Table 2.…”
Section: The Prevalence Of Eipmentioning
confidence: 98%
See 1 more Smart Citation
“…7,9 Wood 13 termed the EIP muscle that attached to the middle and ring fingers as the extensor medii proprius. 14 The incidence of the extensor medii proprius (or extensor indicis et medii) is between 2--5%. 2,7,15 EXTENSOR DIGITI MINIMI (EXTENSOR DIGITI QUINTI)…”
Section: Extensor Indicis Propriusmentioning
confidence: 99%
“…[7][8][9][10] In va ri o us cli ni cal and ana to mi cal stu di es, ana to mic va ri a ti ons, ar ran ge ment and preva len ce of the se ten dons ha ve be en do cu men ted. In li te ra tu re, the in ci den ce of the se musc les and the in ser ti on po ints of the ir ten dons ha ve be en con trover si al.…”
mentioning
confidence: 99%